Digital Revolution and the Shifting Paradigm of Knowledge: Islamic Scholars’ Perspectives on Technology Ethics - Mustaqim, Mustaqim; Ahida, Ridha (Sekolah Tinggi Ilmu Tarbiyah (STIT) Ahlussunnah Bukittinggi, 2025)
The rapid advancement of digital technology has fundamentally transformed the ways knowledge is produced, disseminated, and validated, resulting in significant paradigm shifts across educational, religious, and social domains. This study aims to examine how Islamic scholars construct and negotiate ethical frameworks and knowledge paradigms in response to the digital revolution, particularly in relation to ontological, epistemological, and axiological dimensions of knowledge. Employing a qualitative approach with Critical Discourse Analysis (CDA), this study applies content analysis to examine classical and contemporary Islamic scholarly texts, academic publications, and authoritative digital discourses on technology and ethics. The findings reveal that Islamic scholars perceive the digital revolution as both a challenge and an opportunity: while digitalization disrupts traditional modes of authority and knowledge transmission, it also enables the emergence of more adaptive, inclusive, and context-sensitive models of Islamic scholarship and education. Furthermore, the analysis demonstrates an increasing emphasis on integrating spiritual and moral values with technological innovation to ensure ethical accountability and social benefit. This study implies that the formulation of technology ethics in the digital age requires a holistic integration of Islamic ethical principles with contemporary technological realities, offering a normative framework that promotes human well-being, social responsibility, and the public good.